A Study of Volunteer Community Health Workers Promoting Maternal Health Services in Rural Kenya: A Christian Viewpoint - Bradly Alexander Kimbrough; Lisa Baker (Health for All Nations, 2014)
Introduction: Despite the call for community-based health care interventions in the developing world, there is little research examining the effectiveness of paid versus volunteer community health worker (CHW) programs to increase women's use of maternal health services. From a Christian perspective, the CHW model is, at its root, discipleship: a credible person leads a neighbor to a source of help and health. This effective model can be expanded to address the health of the whole person, both spiritual and physical. This study of a government health center program in rural Kenya addresses these issues. Methods: The current study analyzed the change in maternal health services after a government program, starting with 30 volunteer CHWs, had been in place for nine months. The intervention was designed and carried out by the authors in collaboration with Sigoti District Health Center in the western Kenyan province of Nyanza. Results: The proportion of facility-based deliveries (FBDs) showed a statistically significant increase (p=0.003), from an average of 38 deliveries before the intervention to 60 after-wards. The proportion of health center deliveries of HIV-positive women also significantly increased (p=0.04) from an average of 6.5 to 14 FBDs. Compared to another program in rural Lesotho with paid CHWs, the Sigoti intervention led to a similar increase in FBDs. Despite their successes, the community-based strategies were time-intensive for both programs, with one CHW adding between 1.12 and 1.7 FBDs per year. Discussion: This study demonstrates that a CHW program can be successful, even when using volunteers. Using solely a metric of time and/or money, the CHW model produces value at a high cost. However, the concerns of cost-effectiveness and CHW attrition, as well as the success of the CHW model, can be meaningfully addressed from a Christian perspective. Using the outcome measure of changed lives, volunteer CHWs could be motivated by a Christian call to discipleship. CHWs may be trained and supported to contribute to the health of the whole person. Future research will test these assumptions with a CHW program operating from a Christian health center to be built soon in the study area.